Pengembangan Blog Interaktif yang Disusun Berdasarkan Chronological Thinking sebagai Media Pembelajaran Sejarah di SMA - Wela, Rasmila; Hastuti, Hera (Jurnal Kronologi, 2025)
This research aims to 1) determine the process of developing interactive blogs that are structured based on chronological thinking as a medium for learning history in high school, 2) analyze the feasibility of interactive blogs that are structured based on chronological thinking as a medium for learning history in high school, 3) analyze the practicality of interactive blogs that are structured based on chronological thinking as a medium for learning history in high school and 4) analyze the effectiveness of interactive blogs that are structured based on chronological thinking as a medium for learning history in high school. This is motivated by the limited use of media by teachers, which gives inappropriate thinking among students, such as the view that learning history is monotonous and teacher-centred learning. The method used in this research is Research and Development (R&D) with the ADDIE model. The subjects of this research were 31 students at SMA Negeri 1 Lembah Gumanti. The research results show that interactive blog media has an average feasibility value from material experts of 3.5 and media experts of 3.43. The value of the practicality test by the teacher was 3.8 and the students were 3.63, and finally the results of the effectiveness test of interactive blog media were seen from the analysis of interview answers with students which showed that interactive blog media which was prepared based on chronological thinking was effectively used as a history learning medium in high school.